Challenges in online secure authentication and authorization methodology: a review - Dar, Humaira; Al-Khateeb, Wajdi Fawzi Mohammed; Habaebi, Mohamed Hadi (penseejournal.com, 2013)
Security is one of the major issues in the existing era of modern communication system where the user base has exponentially increased. Currently, majority of the commercial services have switched to internet based services from its conventional pattern for better reachability to end-users. For the purpose of accessing the resources, the user needs to be authenticated and authorized. All the existing web-services are using password based authentication system which has some of the potential loopholes in term of security. This paper basically discusses about the conventional password based authentication schemes and problems associated with it along with discussion on potential perspective of Two-Factor authentication mechanism. The paper has highlighted some of the facts which exhibits that Two-factor authentication system is also shrouded by potential security threats that calls for redefining of security schemes. Finally, the paper contributes in highlighting the open issues associated with the topic.